If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + 3y) * 2 = 0 Reorder the terms for easier multiplication: 2(7 + 3y) = 0 (7 * 2 + 3y * 2) = 0 (14 + 6y) = 0 Solving 14 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 6y = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 6y = 0 + -14 6y = 0 + -14 Combine like terms: 0 + -14 = -14 6y = -14 Divide each side by '6'. y = -2.333333333 Simplifying y = -2.333333333
| 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 | | 61*ln(y)=13 | | 4/3p=9/8 | | 5(2x-6)=25 | | 2(p+9)= | | 4x-3y+z=4 | | 4x+3(2-3x)=40 | | 3x=5+2(3+1x) | | 3(x+3)-3=7(x+1)-4x | | x^3+2x^2+x= | | (x-1)(-6x+6)= | | 7x-5(x+1)+9=19 | | -16.49(4)+5.2= | | ln(5x-13)=4 | | y(2y-8)=0 | | 3(7Y)= | | 5.4(3+2x)-4.2=12 | | 5(x-1)+3(2x-1)=3 | | 4.17x+0.94=3.7x | | 1.7(-9.7x+6)-5= | | 0.1x+0.3= | | 6x-5-1+2x-4x=66 |